2021
DOI: 10.3390/ijerph18168770
|View full text |Cite
|
Sign up to set email alerts
|

Distancing Adherence and Negative Emotions among the Israeli Elderly Population during the COVID-19 Pandemic

Abstract: Social distancing was found to prevent COVID-19 contagion. Therefore, understanding the factors associated with the public’s adherence is important. Acknowledging the importance of emotional wellbeing regarding older people’s health, and understanding their emotional state during the pandemic, are crucial. This study assessed factors associated with older people’s adherence to social distancing and their emotional status. A cross-sectional online survey was conducted among 1822 respondents above the age of 60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…A study among Arabs in Israel found that although higher-educated men whose spouse has a similar educational level shared childcare, this was not the case when the children were babies or toddlers, who require more intensive care, and this might also partly explain the reticence of men to care for the elderly, who are in need of much physical care [23]. In this study, nearly 43% of women did not comply with the mandate to avoid family visits and gatherings, a fact corroborated by Bord and others, who found that among elderly Arabs in Israel, "more than a third reported allowing family members' visitations" [54] (p. 7). They attributed this to their finding that attitudes and perceived social norms were fundamental in predicting distance adherence.…”
Section: Discussionsupporting
confidence: 64%
“…A study among Arabs in Israel found that although higher-educated men whose spouse has a similar educational level shared childcare, this was not the case when the children were babies or toddlers, who require more intensive care, and this might also partly explain the reticence of men to care for the elderly, who are in need of much physical care [23]. In this study, nearly 43% of women did not comply with the mandate to avoid family visits and gatherings, a fact corroborated by Bord and others, who found that among elderly Arabs in Israel, "more than a third reported allowing family members' visitations" [54] (p. 7). They attributed this to their finding that attitudes and perceived social norms were fundamental in predicting distance adherence.…”
Section: Discussionsupporting
confidence: 64%
“…An Israeli study conducted during the first wave of the COVID-19 epidemic in Israel among adults over the age of 60 found that public compliance with the MOH guidelines was high. More than 70% of the respondents reported strictly adhering to the regulations [ 7 ]. Compliance with the preventive measures according to the guidelines is particularly crucial for HCWs, especially at work, in order to protect themselves, their patients, and their families from infection.…”
Section: Introductionmentioning
confidence: 99%
“…Masser Barbara M showed in their research on the willingness of Australian community members to donate that members' coping evaluation (self-efficacy and response efficacy) had a positive predictive effect on their subjective norms and donation attitudes (Masser Barbara M, Hyde Melissa K, & Ferguson Eamonn, 2020). Bord et al found a positive correlation between perceived threat and subjective norms and attitudes in the study of negative emotions in the elderly in the context of the new crown (Bord Shiran et al, 2021). Callens MS et al through attitudes towards migrant integration (multiculturalism and assimilation) and perceptions of threats related to immigrants, the study found that immigrants who have more contact with local people and support cultural assimilation among immigrants with similar cultures are more likely to be threatened by immigrants with longer cultural distances (Marie-Sophie Callens, Bart Meuleman, & Valentová Marie, 2019).…”
Section: Perceived Threat Perceived Efficacy and Subjective Norms Beh...mentioning
confidence: 99%